A secure P2P file sharing model using trust management and data integrity verification. (2016) - Madasamy, N. Senthil; Revathi, T.
Peer-to-Peer (P2P) systems contain a group of equivalent entities that can act as a client, server and overlay network router. P2P file sharing system has become one of the most important internet applications. In this paper, a secure trustworthy P2P file sharing model with novel trust management and data integrity verification strategies is proposed for securing the file sharing between peers. By exploiting the trust value of all peers, the forwarding peer is chosen for file sharing. With the Media Access Control (MAC) level address of the entire file, the final level validation is performed. Further, the file splitting policy reduces the network overhead for the file transmission. The performance comparison of the existing Self-ORganizing Trust (SORT) model with the suggested model shows that the suggested model is optimal than the existing SORT model.